Stroke patient rehabilitation: an analysis of the effects of perturbation training combined with hip unloading gait strategies - Fan, Senchao; Ma, Yiran; Pan, Yu (Frontiers in Neurology, 2025)
BackgroundPerturbation training has been proven effective in reducing the risk of falls in stroke patients. When combined with hip unloading walking training, it may further enhance the restoration of walking and balance functions. This study aims to explore the rehabilitation effects of this combined training strategy on walking disabilities in post-stroke patients, with the goal of providing new methodological guidance for clinical rehabilitation.MethodsA randomized controlled trial was conducted at Beijing Tsinghua Changgung Hospital with stroke patients aged 18–70 years. Thirty patients were included and randomly assigned to three groups: the hip unloading walking group, the hip unloading plus perturbation walking group, and the control group, with 10 patients in each. The effectiveness of the training was assessed before and after using the 10-meter walk test and the Berg Balance Scale, along with secondary indicators including the Fugl-Meyer Assessment for Lower Extremity, Functional Ambulation Categories, three-dimensional gait analysis, and the timed up-and-go test.ConclusionCompared to other types of unloading perturbation training methods, hip unloading training exhibits unique superiority. Perturbation training significantly improved the balance and walking efficiency of stroke patients, especially those with severe balance issues, outperforming traditional rehabilitation methods. The unloading group also showed a positive trend, although it did not reach statistical significance. This demonstrates the potential value of perturbation training in stroke rehabilitation.